Competitive strengthening between dislocation slip and twinning in cast-wrought and additively manufactured CrCoNi medium entropy alloys. (1st March 2023) - Woo, W.; Kim, Y.S.; Chae, H.B.; Lee, S.Y.; Jeong, J.S.; Lee, C.M.; Won, J.W.; Na, Y.S.; Kawasaki, T.; Harjo, S.; An, K.
Abstract: In situ neutron diffraction experiments have been performed under loading in cast-wrought (CW) and additively manufactured (AM) equiatomic CoCrNi medium-entropy alloys. The diffraction line profile analysis correlated the faulting-embedded crystal structure to the dislocation density, stacking/twin fault probability, and stacking fault energy as a function of strain. The results showed the initial dislocation density of 1.8 × 10 13 m −2 in CW and 1.3 × 10 14 m −2 in AM. It significantly increased up to 1.3 × 10 15 m −2 in CW and 1.7 × 10 15 m −2 in AM near fracture. The dislocation density contributed to the flow stress of 470 MPa in CW and 600 MPa in AM, respectively. Meanwhile, the twin fault probability of CW (2.7%) was about two times higher than AM (1.3%) and the stacking fault probability showed the similar tendency. The twinning provided strengthening of 360 MPa in CW and 180 MPa in AM. Such a favorable strengthening via deformation twinning in CW and dislocation slip in AM was attributed to the stacking fault energy. It was estimated as 18.6 mJ/m 2 in CW and 37.5 mJ/m 2 in AM by the strain field of dislocations incorporated model. Dense dislocations, deformation twinning, and atomic-scale stacking structure were examined by using electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). Graphical abstract: Image, graphical abstract